Reforming Higher Education Financing in Armenia - Hauptman, Arthur M.; Barkhudaryan, Levon; Balasanyan, Sergey (International Higher Education, 2011)
Armenia's universities face serious financial challenges. This article focuses on how Armenia has developed new approaching to financing its universities.